Diagnostic Accuracy of Fetal Transverse Cerebellar Diameter (TCD) Measurement as an Individual Parameter for Prediction of Gestational Age in Pregnant Ladies - Kanwal Laique, Syed Mubarak Ali, Ishrat Irfani, Marya Hameed, Shariqullah, Asma Aijaz (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine a relation between fetal transverse cerebellar diameter (TCD) and gestational age from 14 to 36 weeks in pregnant ladies including local population of Karachi from different areas. Methodology: One hundred and seventeen pregnant women were included. The sample size was determined via Online WHO EPI sample size calculator considering the previous study (21) via correlation (r=0.94) with confidence interval 95% and power of test 90%. Booked cases of pregnant women age ranging between 18-40 years with singleton pregnancies of any parity seeking ultrasound for antenatal care were included. Pregnant women with known case of hypertension, diabetes mellitus or diagnosed case of pregnancy induced hypertension or gestational diabetes &fetal structural anomalies were excluded. Demographics and obstetrical data including name, age, parity and relevant records of gestational age from early dating sonographic scan were recorded. Under supervision of expert radiologist in addition to regular biometry parameters T.C.D was also recorded for determination of gestational age. Recorded data was analyzed electronically via SPSS version 22. Results: A quantitative analysis of 117 patients For determination of a correlation between transverse cerebellar diameter (TCD) and gestational age of fetus revealed that out of total 117 pregnant women 29 were primiparous, six were grand multiparous (>5 parity) and the rest were multiparous. Mean ± SD of maternal age was 26.4±4.7 years with minimum 18 and maximum 40 years. Pearson’s correlation coefficient showed that a strong and linear correlation was found among fetal transverse cerebellar diameter & the gestational age i.e. (r=0.99) P<0.005. Conclusion: Between Transverse cerebellar diameter and the gestational age of the fetus between 15 to 36 weeks, a linear correlation was noted. Hence, it can be utilized as a reliable predictor of gestational age. Keywords: Fetal Transverse Cerebellar Diameter, Ultrasound, Gestational Age.